Assessing high school students perceptions and comprehension of climate change - Azeiteiro, Ulisses (2019)
The purpose of this study was to investigate High School (HS) students’ perceptions of Climate Change (CC) and Global warming (GW). This work was conducted within Portuguese High School students and the results in this context should have meaningful implications for national CC policies in the future as well as HS curricula adaptation to the students’ perceptions. Research was conducted at a high school in Central Portugal. The survey was applied to all the high school students from the 10th to the 12th grade, enrolled in the areas of Sciences and Technology, Languages and Humanities, Socio-economical Sciences and Professionalization. The data were collected through a self-completion questionnaire consisting of 29 closed-ended questions and two open questions aiming at characterizing students from the socio-demographic, and from their perceptions, beliefs, motivations, attitudes, knowledge relating to the topic of CC. Google Drive was used to host the questionnaire and allow for the online survey. Statistical exploratory univariate and bivariate analyses were performed on the data collected (frequencies, total and column percentages, adjusted residuals). All statistical tests were two-tailed, with significance levels of 5%. Only statistically significant results were commented on the results section. Majority of students believed that CC was happening and also perceived that human activities were an important cause of CC. Still, the surveyed students hold some misconceptions about basic causes and consequences of climate change. Students’ gender influenced their perceptions of time scale of CC impact on both human and biotic communities. Most students state that their training had focused enough on the topic of CC and felt they had a moderate technical knowledge about the topic of CC (students’ knowledge of how their behaviour influenced CC followed a similar pattern). There was a large conviction that the main actions in mitigating CC effects should be taken by governments and regarding the perception of the importance of CC for their future professional carrier, 48% considered that this topic was “moderately important” and 29% considered it as “very important”. However as individuals, and globally, 74% had not taken actions to mitigate CC (only 26% of the respondents had taken some actions to mitigate the causes of CC). Further research is necessary so that curricula programs can be adequate to promote better knowledge and attitudes about climate change and an active engagement of future participative citizens, as part of the solution for climate change problems.